Performance of managers in the Singapore IPO market : from the viewpoint of issuers and investors - Erh, Jia Jie (2008)
This study seeks to investigate the pricing practice of managers as well as the IPO returns from both issuers’ and investors’ viewpoints. We examine IPOs listed on the SGX within the period 1997 to 2003, and rank their managers based on underpricing, value-weighted underpricing, one-year returns and one-year value-weighted returns.